Immigrants’ Confidence in the Police: An Examination of Generational and Ethnic Differences in the United States - Han, Sungil (International criminal justice review, 2020)
As the number of immigrants in the United States grows, the importance of their confidence in the police cannot be understated. This article simultaneously examines the impact of both generational and ethnic differences among immigrants on their confidence in the police. Using a sample of U.S. residents from the World Value Survey (Wave 6, N = 2,232), the results suggest that first-generation immigrants have less confidence in the police than both nonimmigrants and second-generation immigrants. The results also suggest a generational and ethnic effect with second-generation immigrants of Hispanic/Latino origin reporting a lower level of confidence in the police than other ethnic immigrant groups. The importance of these findings is discussed in light of both scholarly and policy implications.